Onderwysers in die Wes-Kaap se persepsies en belewing van huidige onderwysveranderinge: vir of teen? - Carl, Arend (University of the Free State, 2007)
Within the context of the South African education system, teachers have been confronted with extensive curriculum changes over the past 10 years. The role of the teacher is vital in the successful implementation of new curricula. How do teachers experience and perceive the curriculum changes which have confronted them? An investigation was undertaken into these aspects of change, specifically with regard to Grade 10-12 teachers, who have been exposed to the introduction of the new National Senior Certificate curriculum since 2006. Important findings were made regarding both teachers’ perceptions of the recent curriculum changes. The main argument of this article is that teachers’ perceptions do not necessarily indicate that they are negative about these changes or that they resist them, but that they are influenced by other factors.

Binne die konteks van onlangse kurrikulumverandering ten opsigte van die Suid-Afrikaanse onderwysstelsel is onderwysers die afgelope 10 jaar met omvattende veranderinge gekonfronteer. Die rol van die onderwyser ten opsigte van die suksesvolle implementering van nuwe kurrikula is van kardinale belang. Hoe ervaar onderwysers hierdie verandering en wat is hul persepsies van die kurrikulumverandering waaraan hulle blootgestel word? ’n Ondersoek is geloods om hierdie aspekte te ondersoek, spesifiek ten opsigte van die graad 10-12 onderwysers wat vanaf 2006 blootgestel word aan die infasering van die nuwe Nasionale Senior Sertifikaat-kurrikulum. Belangrike bevindinge is gemaak ten opsigte van onderwysers se persepsies van onlangse kurrikulumveranderinge.
Keywords: South African education system; Teachers; Curriculum changes; New curricula; National Senior Certificate